2007
DOI: 10.1002/da.20270
|View full text |Cite
|
Sign up to set email alerts
|

Partial versus full PTSD in the Korean community: prevalence, duration, correlates, comorbidity, and dysfunctions

Abstract: A few studies have been conducted on the prevalence of partial posttraumatic stress disorder (PTSD), but points of agreement and disagreement between full and partial PTSD have not been fully investigated. We interviewed a representative sample of 6,258 subjects, ages 18-64 years, in household visits using the Korean version of the Composite International Diagnostic Interview (K-CIDI 2.1). "Partial PTSD" was defined as >/=1 symptom in each of the three symptom groups (Criteria B, C, and D) and duration of >/=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
41
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 27 publications
13
41
3
Order By: Relevance
“…While differences between PTSD and subthreshold PTSD were clear, the need for treatment for subthreshold PTSD appears to be warranted. This is especially true in light of previous findings, including the high rates of suicidal ideation, even when controlling for depression (Marshall et al, 2001), and significant impairment (Jeon et al, 2007;Zlotnick et al, 2002). There is a strong evidence base for the successful treatment of PTSD (Foa, Davidson, & Frances, 1999); however the degree to which these techniques may be applied to a subthreshold population has yet to be determined.…”
Section: Discussionmentioning
confidence: 84%
“…While differences between PTSD and subthreshold PTSD were clear, the need for treatment for subthreshold PTSD appears to be warranted. This is especially true in light of previous findings, including the high rates of suicidal ideation, even when controlling for depression (Marshall et al, 2001), and significant impairment (Jeon et al, 2007;Zlotnick et al, 2002). There is a strong evidence base for the successful treatment of PTSD (Foa, Davidson, & Frances, 1999); however the degree to which these techniques may be applied to a subthreshold population has yet to be determined.…”
Section: Discussionmentioning
confidence: 84%
“…This rate is much lower than PTSD rates found in the above studies using checklist methods. Moreover, this rate is considerably lower than PTSD prevalence rates in unaffected populations in other countries based on research using similar structured interview methodology (Alonso et al, 2004;Jeon et al, 2007;Kessler et al, 2005).…”
Section: Studies Using Structured Diagnostic Interviewsmentioning
confidence: 89%
“…Some patients may have symptoms for more than a year, and, to calculate the YLD due to PTSD in this group of patients, information is needed on the maximum duration of the symptoms. The few longitudinal studies that have investigated the course of PTSD in injury patients reported a mean duration of PTSD symptoms of 6–8 years 17 18. In this study, we assumed that the group of patients with long-term PTSD symptoms (>1 year) will experience PTSD symptoms for on average 5.5 years, with a minimum duration of 3 years and maximum duration of 8 years.…”
Section: Methodsmentioning
confidence: 99%